Lexical meaning - Murphy, M. Lynne (Cambridge, [England] Cambridge University Press, 2010)
"The ideal introduction for students of semantics, Lexical Meaning fills the gap left by more general semantics textbooks, providing the teacher and the student with insights into word meaning beyond the traditional overviews of lexical relations. The book explores the relationship between word meanings and syntax and semantics more generally. It provides a balanced overview of the main theoretical approaches, along with a lucid explanation of their relative strengths and weaknesses. After covering the main topics in lexical meaning, such as polysemy and sense relations, the textbook surveys the types of meanings represented by different word classes. It explains abstract concepts in clear language, using a wide range of examples, and includes linguistic puzzles in each chapter to encourage the student to practise using the concepts. 'Adopt-a-Word' exercises give students the chance to research a particular word, building a portfolio of specialist work on a single word"--Provided by publisher.
Part I. Meaning and the lexicon. 1. The lexicon - some preliminaries -- 2. What do we mean by meaning? -- 3. Components and prototypes -- 4. Modern componential approaches - and some alternatives -- Part II. Relations among words and senses. 5. Meaning variation : polysemy, homonymy and vagueness -- 6. Lexical and semantic relations -- Part III. Word classes and semantic types. 7. Ontological categories and word classes -- 8. Nouns and countability -- 9. Predication : verbs, events, and states -- 10. Verbs and time -- 11. Adjectives and properties.
"Reprinted in 2012."--Title page verso.
Keywords: Semantics; Lexicology